Agrarian Landscape Transformations in León Cortés, Costa Rica (1963–2014): Grains, Coffee and Pastures - Solano Mora, Michael David (2025)
Between 1963 and 2014, the canton of León Cortés, located in the Los Santos region, in San José, Costa Rica, underwent substantial changes in its agricultural landscape, including modifications in crop types and farming practices. The cultivated area tripled, driven by the growth of coffee production and the decline of basic cereal crops. Cattle farming also grew during the 1960s and 1970s but reached its peak around the 1984 agricultural census year, after which it began a sharp decline. This article analyzes the transformation in the landscape of the canton through a quantitative methodology supported by agricultural censuses and other statistical sources. The results indicate an increase in the number of farms, land fragmentation up to 1984, followed by a process of land concentration. These transformations are connected to agricultural policies, credit access, global market fluctuations, and environmental programs. The study concludes that coffee specialization reconfigured land use, resulting in tensions between agriculture, livestock farming, and environmental conservation.